INOVASI TALEMPONG GANDANG LASUANG DALAM UPAYA PELESTARIAN SENI TRADISI DI PARIAMAN - Susandrajaya Susandrajaya; Yurnalis Yurnalis; Indriyetti Indriyetti (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Talempong gandang lasuang is a traditional musical ensemble that come from Pariaman. This music usually played by the mature woman during the cooking activity at the wedding party. This art tradition almost extinct, therefore it is necessary to conduct in-depth research to make it revive useful in society. The effort that can be do to make it revive arround the society, we need an innovation and development, therefore it can produce a new form of art, both music and performance aesthetic without eliminating the traditional value. This research uses qualitative method with anthropology approach, sociology, aesthetics and musicologists. Data collection methods that used in this research are observation, interview and documentation. The final result of this research is a new form or composition of ensemble talempong gandang lasuang, which has function and economic value especially for the supporting artist.